Unraveling changes in the duck microbiome and inflammatory processes due to allithiamine-enriched feed - Szőke, Zsombor; Szilágyi-Tolnai , Emese; Dávid, Péter; Fauszt, Péter; Szilágyi, Endre; Szilágyi-Rácz, Anna; Stündl, László; Gál, Ferenc; Gálné Remenyik, Judit; Paholcsek, Melinda (Acta Agraria Debreceniensis, 2024)
The gastrointestinal tract of poultry harbors a diverse and intricate microbiome that plays a crucial role in nutrient digestion and absorption, immune system development, and enhances resistance against pathogens. Maintaining a healthy state and proper production is fundamentally determined by the symbiosis between the host and microbes. Due to genetic and technological improvements, intensive growth rate can be associated with many pathological conditions, such as increased susceptibility to infections. Intestinal inflammation in poultry industries detrimentally affects productivity by hindering nutrient absorption and the efficient allocation of nutrients for growth. The host releases different biomarkers in response to inflammation. Hence, there is an utmost interest of reliable, precise, sensitive and robust biomarkers to evaluate both the gastrointestinal health status and inflammation in poultry. The aim of this study was to determine how the developed feed prototype (allithiamine) affects the community diversity in raised duck, and the relationship between gut microbiome composition and inflammatory factor as calprotectin, using targeted 16S rRNA gene amplicon sequencing and Chicken Calprotectin ELISA Kit.